2017
DOI: 10.1002/bit.26374
|View full text |Cite
|
Sign up to set email alerts
|

Overflow metabolism and growth cessation in Clostridium thermocellum DSM1313 during high cellulose loading fermentations

Abstract: As a model thermophilic bacterium for the production of second-generation biofuels, the metabolism of Clostridium thermocellum has been widely studied. However, most studies have characterized C. thermocellum metabolism for growth at relatively low substrate concentrations. This outlook is not industrially relevant, however, as commercial viability requires substrate loadings of at least 100 g/L cellulosic materials. Recently, a wild-type C. thermocellum DSM1313 was cultured on high cellulose loading batch fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 70 publications
0
30
0
Order By: Relevance
“…Pyruvate accumulation and subsequent overflow metabolism has been observed and studied in detail in C. thermocellum (Deng et al., ; Holwerda et al., ; Olson et al., ; Thompson et al., ). Accumulation of formate and hydrogen in C. thermocellum collectively restrict the reoxidation of ferredoxin and limit its availability for pyruvate:ferredoxin oxidoreductase‐enabled conversion of pyruvate to acetyl‐CoA, causing accumulation of pyruvate and pyruvate‐derived overflow metabolism products (Holwerda et al., ; Thompson & Trinh, ; Thompson et al., ). C. cellulolyticum growth was shown to be inhibited by high concentrations of NADH, which inhibits glyceraldehyde 3‐phosphate dehydrogenase activity and limits glycolytic flux (Payot, Guedon, Cailliez, Gelhaye, & Petitdemange, ).…”
Section: Discussionmentioning
confidence: 99%
“…Pyruvate accumulation and subsequent overflow metabolism has been observed and studied in detail in C. thermocellum (Deng et al., ; Holwerda et al., ; Olson et al., ; Thompson et al., ). Accumulation of formate and hydrogen in C. thermocellum collectively restrict the reoxidation of ferredoxin and limit its availability for pyruvate:ferredoxin oxidoreductase‐enabled conversion of pyruvate to acetyl‐CoA, causing accumulation of pyruvate and pyruvate‐derived overflow metabolism products (Holwerda et al., ; Thompson & Trinh, ; Thompson et al., ). C. cellulolyticum growth was shown to be inhibited by high concentrations of NADH, which inhibits glyceraldehyde 3‐phosphate dehydrogenase activity and limits glycolytic flux (Payot, Guedon, Cailliez, Gelhaye, & Petitdemange, ).…”
Section: Discussionmentioning
confidence: 99%
“…This thermophile was chosen, because it has a high cellulolytic activity suitable for CBP, a one-step process configuration for cellulase production, cellulose hydrolysis, and fermentation for direct conversion of lignocellulosic biomass to fuels and chemicals [27]. Furthermore, studies have demonstrated that the wild-type C. thermocellum has native metabolism capable of endogenously producing precursor metabolites for ester biosynthesis, such as acetyl-CoA, isobutyryl-CoA, as well as ethanol [28] and higher alcohols (e.g., isobutanol) under high cellulose loading fermentation [29][30][31] (Fig. 4a, Additional file 1: Figure S5A).…”
Section: Isobutyl Acetate Production From Cellulose At Elevated Tempementioning
confidence: 99%
“…The isobutanol pathway can consume NADPH through several enzymes 6 and has increased flux during overflow metabolism at high-substrate loading. 18,37 The model also predicted a decrease in valine secretion (EX val L e), since the isobutanol path-way competes with the valine pathway after KARA1. Remarkably, this prediction is consistent with the lower valine secretion measured in Δ hydG Δ ech .…”
Section: Resultsmentioning
confidence: 90%
“…17 The iAT601 model was used to identify genetic manipulations for high ethanol, isobutanol, and hydrogen production, 16 and to understand growth cessation prior to substrate depletion observed under high-substrate loading fermentations that simulate industrial conditions. 18 In addition to these core and genome-scale steady-state metabolic models, a kinetic model of central metabolism, k-ctherm118, was recently developed and used to elucidate the mechanisms of nitrogen limitation and ethanol stress. 15 Due to the biotechnological relevance of the Clostridium genus, GSMs have also been developed for other species, 19 including C. acetubutylicum , 2026 C. beijerinckii , 27 C. butyricum , 28 C. cellulolyticum , 22 and C. ljungdahlii .…”
Section: Introductionmentioning
confidence: 99%